Mediação implícita da informação para a justiça social na arquivologia: o guia para usuários/as de arquivos como instrumento de interferências transformadoras - Araújo, Vitor Hugo Teixeira (2024)
Archival institutions bear the social responsibility of ensuring access to documents through finding aids, which represent the content of these records. In this context, the user guide for archives serves not only to inform but also to promote the archive within communities. However, it is considered problematic that this tool often does not receive the deserved attention from archivists, hindering its potential to mediate information in the Global South. Therefore, intervening in this scenario, actions are enhanced by Southern Epistemologies – which critique the suppression of knowledge by dominant norms and advocate for social justice as a tool to recognize systemic and structural inequalities, offering alternatives to amplify diverse voices within archives. Based on this, the following research question is established: How can the user guide for archives, through implicit representation and mediation of information, be leveraged by archivists to promote social justice in the Global South? Thus, the general objective is to propose strategies, informed by Southern Epistemologies, for implicit mediation of information in favor of social justice through the user guide for archives. Specific objectives include: contextualizing Southern Epistemologies within the fields of Information Science and Archival Studies; discussing information mediation in Archival Studies, particularly in archival description practices in Brazil; strengthening discussions on information representation within Archival Studies as a practice of implicit information mediation; and debating social justice within Archival Studies, specifically in processes of implicit information mediation through the user guide for archives. Methodologically, this study is a basic, descriptive, qualitative, and bibliographic-documentary research that analyzes theoretical production on the research themes without temporal constraints, through content analysis. Results demonstrate that while contemporary discussions broaden archival objectives towards social interests, the limited research on information mediation and social justice within these institutions hampers policy development that could enhance their societal role, whether through structural investments or fostering community engagement. Thus, grounded in an intercultural, anticolonial, and counter-hegemonic perspective, the study proposes updated forms of implicit information mediation through the user guide, emphasizing that its full implementation transcends rigorous archival description criteria to include planning, implementation, dissemination, and evaluation strategies that collectively advance the struggle for social justice. The study concludes that achieving emancipatory outcomes through the user guide requires archivists to flexibly expand their scope of action, prioritizing certain responsibilities previously not attributed to their role. This flexibility does not diminish their archival duties but expands the understanding of Archival Studies, contributing to a more just society as a shared responsibility.